Respiration-Deficient Astrocytes Survive As Glycolytic Cells In Vivo - Supplie, Lotti M. (J Neurosci, 2017)
Neurons and glial cells exchange energy-rich metabolites and it has been suggested, originally based on in vitro data, that astrocytes provide lactate to glutamatergic synapses (“lactate shuttle”). Here, we have studied astrocytes that lack mitochondrial respiration in vitro and in vivo. A novel mouse mutant (GLAST(CreERT2)::Cox10(flox/flox)) was generated, in which the administration of tamoxifen causes mutant astrocytes to fail in the assembly of mitochondrial cytochrome c oxidase (COX). Focusing on cerebellar Bergmann glia (BG) cells, which exhibit the highest rate of Cre-mediated recombination, we found a normal density of viable astrocytes even 1 year after tamoxifen-induced Cox10 gene targeting. Our data show that BG cells, and presumably all astrocytes, can survive by aerobic glycolysis for an extended period of time in the absence of glial pathology or unspecific signs of neurodegeneration. SIGNIFICANCE STATEMENT When astrocytes are placed into culture, they import glucose and release lactate, an energy-rich metabolite readily metabolized by neurons. This observation led to the “glia-to-neuron lactate shuttle hypothesis,” but in vivo evidence for this hypothesis is weak. To study astroglial energy metabolism and the directionality of lactate flux, we generated conditional Cox10 mouse mutants lacking mitochondrial respiration in astrocytes, which forces these cells to survive by aerobic glycolysis. Here, we report that these mice are fully viable in the absence of any signs of glial or neuronal loss, suggesting that astrocytes are naturally glycolytic cells.